Pharmacological safety profile and hemocompatibility of lipid nanocarrechers based on tucuman butter - Silveira, Larissa da Silva; Rossato, Aline; Oliveira, Pâmella Scharamm; Fonseca, Elisandra da Silva Pena da; Bortoluzzi, Luisa Donato; Vieira, Wanessa de Carvalho; Kurtz, Guilherme Chagas; de Souza Filho, Walter Paixão; Souza, Diego; Sagrillo, Michele Rorato (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
With the growing need to develop effective and sustainable therapeutic alternatives, research has been focusing on the association of products of natural origin with nanotechnology, which besides enhancing the action, acts to protect the constituents from degradation. A fruit highlighted in research today is Astrocaryum vulgare (Tucumã), as well as natural fixed oils extracted from seeds, such as grape seed oil and microalgae biomass. The present study aimed to evaluate the parameters of pharmacological safety and in vitro hemocompatibility of lipid nanocarriers (CLN) from the association of tucumã butter with two oils (grape seed and microalgae). Hemocompatibility rates were assessed by analyzing hemolytic activity, in addition to clotting time and clot retraction, whereas pharmacological safety analyzed parameters such as cell viability, DNA damage, dichloride and nitric oxide production. The nanocarriers produced through the association of butter with oils showed a satisfactory pharmacological safety and hemocompatibility profile.